Currency union and investment flows: Estimating the euro effect on FDI - Marián Dinga; Vilma Dingová (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper studies the effect of the euro introduction on international FDI flows. Using country-pair data on 35 OECD economies during 1997-2008 and adopting the propensity score matching as identification strategy, we investigate the impact of the euro on capital reallocation. In general, the euro exhibits no significant impact on FDI. However, the effect becomes significant on the subset of EU countries, increasing FDI flows by 14.3 to 42.5 percent. Furthermore, we find that the EU membership fosters FDI flows much more than the euro, increasing FDI flows by 55 to 166 percent. Among other FDI determinants, high gross domestic product, low distance between countries and low unit labor costs in target country have a positive effect on FDI. On the contrary, long-term exchange rate volatility deters FDI flows.
Keywords: E42; F15; F21; 330; monetary union; foreign direct investment; common currency area; euro